Neonatal outcomes of preterm neonates and its predictors in Ethiopian public hospitals: Multicenter prospective follow-up study - Habtamu Shimels Hailemeskel; Fentaw Teshome Dagnaw; Solomon Demis; Binyam Minuye Birhane; Melkalem Mamuye Azanaw; Ermias Sisay Chanie; Worku Necho Asferie; Metsihet Tariku Fetene; Ayenew Mose; Demeke Mesfin Belay; Demewoz Kefale; Amare Kassaw; et al. (Heliyon, 2023)
Introduction: Preterm birth remains the most significant clinical and public health encounter. Preterm infant outcomes pose key evidence for clinicians and policymakers and are extensively used to set clinical and policy verdicts to improve services. It is necessary to conduct the outcomes of neonates frequently, as it varies from place to place and even from time to time in a similar place. There is limited literature in Ethiopia about preterm neonates’ outcomes and their predictors. Objective: This study aimed to assess the neonatal outcomes of preterm neonates and their predictors in South Gondar zone public hospitals, Northwest Ethiopia, 2021. Methods: A prospective observational study was employed on 462 preterm neonates in South Gondar Zone Public Hospitals. The data were entered into Epidata 4.6 and analyzed using STATA version 16/MP software. A parametric log-normal survival model was used to identify possible predictors for preterm neonate death. Statistical significance was declared at a P-value less than 0.05. Result: The overall preterm survival rate was 71.1% (95% CI: 66.7, 75.1). Thirty-six percent of preterm neonates were diagnosed with sepsis. One-fourth of the neonates had respiratory distress syndrome. Gestational age greater than 34 weeks (β = 1.04; 95% CI: 0.53, 1.56), respiratory distress syndrome (β = 0.85; 95% CI: 0.49, 1.22), body mass index (β = −1.34; 95% CI: −1.87, −0.80), non-union marital status (β = −0.71; 95% CI: −1.34, −0.09), multiple pregnancies (β = −0.66; 95% CI: −0.99–0.32), multiparous (β = 0.35; 95% CI: 0.01, 0.69), hypothermia (β = −1.19; 95% CI: −1.76, −0.62), Kangaroo Mother Care (β = −1.9; 95% CI: −2.34, −1.41) and non-cephalic presentation (β = −1.23; 95% CI: −1.99,-0.46) were significant predictors. Conclusion: In this study, the preterm survival rate was low. Gestational age greater than 34 weeks, no respiratory distress syndrome, and multiparous mothers were positively associated with the survival of preterm neonates. Though, high pre-pregnancy maternal body mass index, non-union marital status of mothers, multiple pregnancies, hypothermia, Kangaroo mother care is not given, and non-cephalic presentation were negatively associated. A significant focus should be given to implementing WHO recommendations on preventing and caring for preterm births.